PIN proteins perform a rate-limiting function in cellular auxin efflux - Petrášek, Jan; Mravec, Jozef; Bouchard, Rodolphe; Blakeslee, Joshua J; Abas, Melinda; Seifertová, Daniela; Wisniewska, Justyna; Tadele, Zerihun; Kubeš, Martin; Čovanová, Milada; Dhonukshe, Pankaj; Skůpa, Petr; et al. (Science, 2006)
Intercellular flow of the phytohormone auxin underpins multiple developmental processes in plants. Plant-specific pin-formed (PIN) proteins and several phosphoglycoprotein (PGP) transporters are crucial factors in auxin transport-related development, yet the molecular function of PINs remains unknown. Here, we show that PINs mediate auxin efflux from mammalian and yeast cells without needing additional plant-specific factors. Conditional gain-of-function alleles and quantitative measurements of auxin accumulation in Arabidopsis and tobacco cultured cells revealed that the action of PINs in auxin efflux is distinct from PGP, rate-limiting, specific to auxins, and sensitive to auxin transport inhibitors. This suggests a direct involvement of PINs in catalyzing cellular auxin efflux.
Keywords: mutace; financování organizované; ATP-Binding Cassette Transporters; HeLa Cells; biologický transport; kyseliny naftalenoctové; Kinetics; Arabidopsis Proteins; Membrane Transport Proteins; Saccharomyces cerevisiae; Naphthaleneacetic Acids; transfekce; Transfection; membránové transportní proteiny; Nicotiana; Indoleacetic Acids; lidé; HeLa buňky; ABC transportéry; Mutation; transformace genetická; kultivované buňky; proteiny huseníčku; Financing, Organized; Biological Transport; Cells, Cultured; ftalimidy; Plant Roots; kyseliny indoloctové; Phthalimides; Transformation, Genetic; Arabidopsis; buněčná membrána; kořeny rostlin; tabák; Gravitropism; kinetika; gravitropismus; Cell Membrane; Humans